Spontaneous knee effusion in an adolescent soccer player - Buckley, B. D.; Joyce, C. J. (International Journal of Athletic Therapy & Training, 2021)
A 13-year-old female recreational soccer player presented with spontaneous left knee effusion approximately 2 weeks after the start of soccer season. Radiographic imaging was negative, and a complete blood count identified an increase in inflammatory markers. Additional two-tier testing confirmed a Lyme disease diagnosis, which was unusual for an athlete residing in the southeast region of the United States. The presentation of knee effusion, and subsequently Lyme arthritis, is a common clinical manifestation of late-stage Lyme disease. Early recognition of this infection and prompt treatment by a variety of specialists reduce the severity or chronicity of symptoms.